A comparative analysis between two Philippine and two Latin American magic realist novels. - Prescott, Julie
This creates a clearer understanding of Philippine Magic realism through a comparative analysis of two Philippine and Two Latin american Magic realist novels. The true definition of Magic realism has always been blurry; Therefore the proponent uses Zamora and Faris definition of Magic realism and identifies its elements in th enovel., To this end, this study falls into two parts, one is concerned with the understanding of realism through the discussion of the elements in the four selected novels: Memories of My Melancholy Whores, The House of the Spirits, Salamanca, and Great Philippine Jungle Energy Cafe by Gabirel Garcia Marquez, Isabel Allende, Dean Francis Alfar, and Alfred Yuson respectively; and second part is a comparative analysis between Latin American and Philippine magic realist texts that reveals their differences and similarities. The conclusion turns to the examination the findings which show that although there are obvious similarities in the texts, origin and cultural backgrounds result in huge differences between the two and make Philippine texts unique in their own right.